Avaliação da citotoxicidade e do potencial bioativo do óleo de buriti (Mauritia flexuosa L. f.) nanoencapsulado em gelatina suína - Morais, Neyna Santos (2021)
Buriti oil is extracted from the fruit of the buriti tree (Mauritia flexuosa L.f.). It is rich in carotenoids, especially β-carotene, in addition to tocopherols, unsaturated fatty acids, other nutrients, and bioactive compounds that have antioxidant and antimicrobial characteristics. The sensitivity to factors such as light, heat, humidity, pH, and oxygen that buriti oil and bioactive compounds have and the lipophilic nature of the oil justify the use of nanoencapsulation to preserve and enhance the oil's bioactive properties. The present study aimed to evaluate the cytotoxicity, antioxidant potential, and antimicrobial effect on the modulation of the antibiotic activity of porcine gelatin nanoparticles containing buriti oil (OPG). The nanoformulation was obtained through the O/W emulsification technique, using porcine gelatin as an encapsulating agent and Tween 20 as a surfactant. Characterization was performed by Scanning Electron Microscopy (SEM), Dynamic Light Scattering (DLS), and Fourier Transform Infrared Spectroscopy (FTIR), in addition to evaluating the encapsulation efficiency (%). The cytotoxicity analysis was performed on Chinese Hamster Ovary Cells (CHO) using the MTT test ((3-(4,5-Dimethylthiazol-2-yl) -2,5- Diphenyltetrazolium Bromide). The antioxidant potential of free buriti oil and OGS was determined by different in vitro methods, such as total antioxidant capacity (TAC), reducing power, and scavenging to ABTS radical. The evaluation of the modulating antimicrobial activity was performed by determining the minimum inhibitory concentration (MIC), using Gram-negative (Escherichia coli and Pseudomonas aeruginosa) and Gram-positive (Staphylococcus aureus) bacteria and two antibiotics, gentamicin and norflaxacillin. The SEM showed spherical particles with smooth and uniform. The particle size and polydispersion index (PI) obtained through Dynamic Light Scattering (DLS) were 72 nm e 0,371nm, respectively. The FTIR showed chemical interactions in OPG due to displacement and formation of new vibrational bands, indicating the interaction of oil with porcine gelatin and confirming encapsulation. The encapsulation efficiency obtained was 89.56%. The cytotoxicity analysis showed that crude buriti oil and OPG did not show a cytotoxic effect on CHO cells. The results of the antioxidant activity showed that for both the TAC test and the reducing power, OPG presented greater antioxidant activity when compared to free buriti oil (p < 0.05). For the modulating antimicrobial activity, it was observed that the combination of antibiotics, norfloxacillin and gentamicin, with free buriti oil and OPG, was more efficient in inhibiting E. coli and P. aeruginosa compared to isolated antibiotics (p < 0 .05). Regarding the inhibition of S. aureus, OPG stood out in combination with norfloxacillin, reducing MIC by 50%. Thus, it was observed that nanoencapsulation increased the antioxidant potential and antimicrobial activity of buriti oil, which can be explained by the protection given to bioactive compounds with these properties.